Analisis Sistem Penjualan Beras Bulog di Perum Bulog Kantor Wilayah Kota Jambi - Tamara, Vidiya; Suandi, Suandi; Ningsih, Rozalina (Universitas Batangahari Jambi, 2025)
Perum Bulog is a state-owned enterprise (SOE) tasked with maintaining the availability and stability of food prices, particularly rice. Nevertheless, consumer preferences and satisfaction regarding Bulog rice in Jambi City remain questionable, especially concerning perceptions of the sales system. This study aims to analyze the rice sales system of Bulog at the Jambi Regional Office. This research employs a quantitative approach with a descriptive method, through the collection of primary and secondary data. The results show that the Bulog rice sales system is carried out through two main channels, namely direct and indirect sales. Direct sales include, the Affordable Market Movement program (Gerakan Pasar Murah/GPM), Market Operations (OP) onsignment system, distribution through public markets, as well as payment schemes such as Cash Before Delivery (CBD), Cash on Delivery (COD), and deferred payment. Meanwhile, indirect sales are carried out through distribution agents, retailers, and food aid distribution in government social programs. Direct sales have proven effective in providing SPHP rice at affordable prices for low-income communities. However, distribution still faces challenges such as limited stock at GPM locations, uneven information dissemination, and weak distribution coordination. To overcome hese obstacles, Perum Bulog has begun to utilize digital technology such as social media and WhatsApp groups in villages to rapidly and widely disseminate information to the public. These findings indicate that strengthening the distribution system, utilizing information technology, and continuous evaluation of the food subsidy program are keys to improving the effectiveness of the Bulog rice sales system in Jambi City.